Studi kasus keberhasilan kebijakan Umar bin Abdul Aziz dan kegagalan gubernur Nasar bin Sayyar pada masa khalifah Marwan II - Tafziyah, Salfa Nurul (Maliki Interdisciplinary Journal, 2024)
The purpose of this article is to find out the successes and failures of policies in the Umayyad era. The research method in this article is qualitative, while the analysis method in this article is descriptive qualitative analysis by examining various sources related to policies in the Umayyad era. The results or findings of this research are that leadership in history often produces a striking impact on the development of a country. There are two important figures in the history of the Umayyad Caliphate, namely Caliph Umar bin Abdul Aziz and Caliph Umar bin Sayyar, both of whom provide a contrasting picture of the success and failure of leadership in different contexts. This article will discuss and analyze the factors that led to the success of Caliph Umar bin Abdul Aziz and the failure of Caliph Umar bin Sayyar during the reign of Caliph Marwan II.